Model Lokasi-Alokasi Bantuan Logistik Catastrophic Berbasis Masjid di Kota Padang - Nofa Ariyana (Jurnal Optimasi Sistem Industri, 2012)
Padang is one of the most vulnerable area of earthquake and tsunami in Indonesia. Therefore, it is necessary to have a good strategic planning about disaster logistics system and contingency planning. Contigency planning have three factors, human resources, transportation, and inventory. The problems that happened at distribution of disaster logistical buffer between distribution centre (BPBD Padang) and evacuation post are needed a buffer post (assistant post). This research suggest a location allocation model to select buffer post location and logistics allocation that distributed to evacuation post with minimum cost.